Larvicidal properties of terpenoid-based nanoemulsions against the dengue vector Aedes aegypti L. and their potential toxicity against non-target organism - Duarte, Jonatas Lobato [UNESP]; Duchon, Stéphane; Filippo, Leonardo Delello Di [UNESP]; Chorilli, Marlus [UNESP]; Corbel, Vincent (Public Library of Science (PLoS), 2024)
The development of insecticide resistance in mosquitoes of public health importance has encouraged extensive research into innovative vector control methods. Terpenes are the largest among Plants Secondary Metabolites and have been increasingly studied for their potential as insecticidal control agents. Although promising, terpenes are insoluble in water, and they show low residual life which limits their application for vector control. In this study, we developed and evaluated the performances of terpenoid-based nanoemulsions (TNEs) containing myrcene and p-cymene against the dengue vector Aedes aegypti and investigated their potential toxicity against non-target organisms. Our results showed that myrcene and p-cymene showed moderate larvicidal activity against mosquito larvae compared to temephos an organophosphate widely used for mosquito control. However, we showed similar efficacy of TNEs against both susceptible and highly insecticide-resistant mosquitoes from French Guyana, hence suggesting an absence of cross-resistance with conventional insecticides. We also showed that TNEs remained effective for up to 45 days in laboratory conditions. The exposure of zebrafish to TNEs triggered behavioral changes in the fish at high doses but they did not alter the normal functioning of zebrafish organs, suggesting a good tolerability of non-target organisms to these molecules. Overall, this study provides new insights into the insecticidal properties and toxicity of terpenes and terpenoid-based formulations and confirms that TNE may offer interesting prospects for mosquito control as part of integrated vector management.